2005
DOI: 10.3748/wjg.v11.i42.6644
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 in peptic ulcer disease: An inverse association withHelicobacter pylori

Abstract: HSV-1 is frequent in upper gastro-intestinal tract ulcers but not in normal gastric and duodenal mucosa. There is an inverse association between HSV-1 and H pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…However, this was not determined by the current study. Tsamakidis et al 47 showed that there was an inverse association between HSV-1 and H. pylori infection in patients with gastrointestinal tract ulcers. However, Baccaglini et al 48 suggested that HSV-1 seropositivity was associated with a higher H. pylori seroprevalence.…”
Section: Resultsmentioning
confidence: 99%
“…However, this was not determined by the current study. Tsamakidis et al 47 showed that there was an inverse association between HSV-1 and H. pylori infection in patients with gastrointestinal tract ulcers. However, Baccaglini et al 48 suggested that HSV-1 seropositivity was associated with a higher H. pylori seroprevalence.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 There is also a report of the presence of the herpes simplex virus in H pylori-negative ulcers, although the nature of the association is unclear. 29 Cameron and Higgins 30 reported ulceration of the proximal stomach in patients with hiatus hernia and occurring where the gastric mucosa passes through the diaphragmatic hiatus. These ulcers were associated with iron deficiency anemia, although the nature of the association is unclear.…”
Section: Management Of Patients With Apparent H Pylori-negative Nonstmentioning
confidence: 98%
“…Some conditions, such as Crohn’s disease, amyloidosis, sarcoidosis, eosinophylic gastroenteritis, lymphoma, Schonlein‐Henoch purpura or some infections (such as cytomegalovirus or herpes simplex) may cause ulceration of the duodenal mucosa 14, 20, 22, 93, 103, 114, 165–172 . Although ulcers of the stomach are routinely biopsied to exclude cancer, this is not the standard practice for duodenal ulceration.…”
Section: Explanations For Helicobacter Pylori‐negative Ulcersmentioning
confidence: 99%